Analysis of MMP2 promoter polymorphisms in childhood obesity - Morgan, Angharad R (BioMed Central, 2011)
BACKGROUND: Several lines of evidence suggest a possible functional role of Matrix metalloproteinase -2 (MMP-2) in obesity. The aim of this study was to evaluate the role of MMP-2 promoter polymorphisms in percentage body fat (PBF) as a measure of childhood obesity in a New Zealand population. FINDINGS: 546 samples from the Auckland Birthweight Collaborative (ABC) study were genotyped for the three MMP-2 promoter SNPs -1306 C/T (rs243865), -1575G/A (rs243866) and -790 T/G (rs243864) using the Sequenom genotyping platform. The results demonstrated that an MMP-2 promoter haplotype is associated with PBF in New Zealand 7 year old children. CONCLUSION: We have previously determined that environmental factors are associated with differences in PBF in this study group, and now we have demonstrated a possible genetic contribution.